2012
DOI: 10.1039/c2fo10260a
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the fate of chlorogenic acids in coffee roasting using mass spectrometry based targeted and non-targeted analytical strategies

Abstract: Coffee is one of mankind's most popular beverages obtained from green coffee beans by roasting. Much effort has been expended towards the chemical characterisation of the components of the roasted coffee bean, frequently termed melanoidines, which are dominated byproducts formed from its most relevant secondary metabolites - chlorogenic acids. However, impeded by a lack of suitable authentic reference standards and analytical techniques sufficiently powerful for providing insight into an extraordinarily comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 36 publications
6
97
0
Order By: Relevance
“…In case of 3-CSA, the calculated energy to cleave C9′–O bond was approximately 74 kcal·mol −1 (3.21 eV), whereas the energies required to cleavage C3–O, C4–O and C5–O bonds were 48, 58 and 56 kcal·mol −1 (2.08, 2.52 and 2.43 eV), respectively. The breakdown curve for the three regioisomeric caffeoylshikimate showed that the cleavage energy was C3–O < C5–O < C4–O [19]. Thus, cleavages of C3–O, C4–O and C5–O bonds were easier than the cleavage of C9′–O bond.…”
Section: Resultsmentioning
confidence: 99%
“…In case of 3-CSA, the calculated energy to cleave C9′–O bond was approximately 74 kcal·mol −1 (3.21 eV), whereas the energies required to cleavage C3–O, C4–O and C5–O bonds were 48, 58 and 56 kcal·mol −1 (2.08, 2.52 and 2.43 eV), respectively. The breakdown curve for the three regioisomeric caffeoylshikimate showed that the cleavage energy was C3–O < C5–O < C4–O [19]. Thus, cleavages of C3–O, C4–O and C5–O bonds were easier than the cleavage of C9′–O bond.…”
Section: Resultsmentioning
confidence: 99%
“…MS fragmentation patterns, under different ionization modes, have been employed in chemical analysis, including analysis of components of coffee [148]. Direct analysis in real time (DART) coupled to time-of-flight mass spectrometry (TOFMS) yielded a high throughput (<1 min per run) analysis of caffeine in coffee samples [101].…”
Section: Methods For Characterization and Quantification Of Bioactmentioning
confidence: 99%
“…Coffee products and apple are among those sources constituting high percentage of CQAs [1][2][3]. Some vegetables, for example, sweet potato and leeks also constitute these compounds [4,5].…”
Section: Introductionmentioning
confidence: 99%